Static and modal numerical analyses for the roof structure of a railway freight refrigerated car - Raffaele Sepe; Angela Pozzi (Fracture and Structural Integrity)
Numerical analyses by finite element method and experimental tests are used to determine static and dynamic behaviour of railway vehicles. Experimental measurements are very time consuming and expensive, so they cannot be used at all stages of design. Numerical simulations do not have the disadvantages of experimental methods, but it is necessary to verify them by experiments to obtain realistic results. Fullwidth/ full-length, half-width/full-length and half-width/half-length modeling approaches can be used to determine static and vibrational behaviours of railway vehicles depending or not on the symmetry of roof structure and applied load. Different static loading cases defined in standards such as EN 12663, UIC CODE OR 577 and ERRI B12/RP17 have to be considered in FE analyses. Evaluation of stress states, buckling and vibrational behaviours for a roof structure of a railway freight refrigerated car are presented. To highlight the vibrational behaviour of the structure normal mode (free vibration) analyses are performed. As a result of the relevant simulations, structural characteristics and structural weaknesses of the design are determined.